Studies on the Origin of Harmonic Tonality - Dahlhaus, Carl (Book collections on Project MUSE., 2014)
Carl Dahlhaus was without doubt the premier musicologist of the postwar generation, a giant whose recent death was mourned the world over. Translated here for the first time, this fundamental work on the development of tonality shows his complete mastery of the theory of harmony. In it Dahlhaus explains the modern concepts of harmony and tonality, reviewing in the process the important theories of Rameau, Sechter, Ftis, Riemann, and Schenker. He contrasts the familiar premises of chordal composition with the lesser known precepts of intervallic composition, the basis for polyphonic music in.